(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Chylous ascites is the extravasation of milky chyle into the peritoneal cavity. This can occur de novo as a result of trauma or obstruction of the lymphatic system. Moreover, an existing clear ascitic fluid can turn chylous as a secondary event. True chylous ascites is defined as the presence of ascitic fluid with high fat (triglyceride) content, usually higher than 110 mg/dL. A cases report was done on a 3 months infant with chylous ascitis diagnosed after ascetic fluid paracentesis at the pediatric department in Tikrit teaching hospital at 13 of March 2011. The aim of this report is to describe the clinical and biochemical features of a patient with chylous ascitis. The patient was presented with huge abdominal distention associated with scrotal swelling for the last one month. Examination shows scrotal edema with bilateral indirect inguinal hernia with positive shifting dullness and transmitted thrill signs ( which indicates presence of a fluid inside the peritoneal cavity). No umbilical hernia or peripheral edema. Abdominal ultrasound shows huge ascitis with bilateral indirect inguinal hernia and no organomegaly. Chest X-ray was normal . complete blood picture and renal function test were normal. Serum electrolyte was normal liver function test was normal except for serum albumin which was low. Paracentesis was done under full aseptic technique which revealed a milky ascetic fluid under very high pressure. The sample was divided into three parts . the first part is for biochemical analysis which revealed a high protein , triglyceride and specific gravity. The second part was sent for cytology and acid fast bacilli which shows increased cellularity with no abnormal cells) and negative test for acid fast bacilli. The third part was send for culture and sensitivity and it was negative. Abdominal CT scan was not done till this time because of the long appointment given for the patient on the waiting list at Tikrit teaching hospital . Lymphangiogram was not done because it is not available in Iraq till now. The patient was put on conservative treatment with follow up regarding the need for paracentesis if there is respiratory compromise by the ascetic fluid and for diet modification after the child starts feeding.